Female development in the autobiographical novel of Fang E’zhen - Lim, Choon Bee (2016)
Fang E’zhen, a Chinese Malaysian female writer, was greatly admired in the literary arenas of both Malsysia and Taiwan in the 1970s and 1980s. the renowned poet Yu Kwang-chung once praised her as “the most endearing little girl of Muse.” Yu’s recognition has virtually shaped the public image of Fang E’zhen. However, has the “little girl” ever grown up or at least has the notion of growing up? Hua Tianya, a novel by Fang, which exhibits a distinct voice of auto diegetic narration, no doubt is an ideal text to clarify this question. It depicts the living conditions of women in particular circumstances through an apparel “feminine” language and style, and to an extent reveals the life experiences of Chinese Malaysian female in the 1960s and 1970s. based on this autobiographical novel, this paper aims to discuss the above questions from the aspects of female subjectivity and cultural identity.